2003
DOI: 10.1177/0886260503251070
|View full text |Cite
|
Sign up to set email alerts
|

Rape Prevention With College Males

Abstract: This study investigated the immediate impact of a video-based prevention program developed to decrease undergraduate men’s potential to commit rape. Three video segments (rape myth acceptance, victim empathy, and outcome expectancies) were developed through expert consultation and focus groups. Evidence for the construct validity of each component was evaluated by examining change scores in a pilot study of 101 male undergraduates on measures of rape myth acceptance, victim empathy, and outcome expectancies. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Campus-based sexual assault programs can also target students, particularly those groups who may be at risk of offending (White & Smith, 2004). Programs offered by campus-based sexual assault centers have been evaluated and the results of these evaluations suggest that sexual assault prevention programs can change attitudes about rape and reduce the risk of victimization (Forst, Lightfoot, & Burrichter, 1996;Johansson & Geer, 2003;O'Donohue, Yeater, & Fanetti, 2003). Campus-based programs have been criticized for their overall lack of emphasis on self-defense training (Sochting, Fairbrother, & Koch, 2004).…”
Section: Review Of Literaturementioning
confidence: 97%
“…Campus-based sexual assault programs can also target students, particularly those groups who may be at risk of offending (White & Smith, 2004). Programs offered by campus-based sexual assault centers have been evaluated and the results of these evaluations suggest that sexual assault prevention programs can change attitudes about rape and reduce the risk of victimization (Forst, Lightfoot, & Burrichter, 1996;Johansson & Geer, 2003;O'Donohue, Yeater, & Fanetti, 2003). Campus-based programs have been criticized for their overall lack of emphasis on self-defense training (Sochting, Fairbrother, & Koch, 2004).…”
Section: Review Of Literaturementioning
confidence: 97%
“…Topics that were commonly covered include the legal definitions of rape and sexual assault (Schewe & O'Donohue, 1993, an in-depth analysis of rape as a violent crime (O'Donohue, Yeater, & Fanetti, 2003), and discussion about the actual prevalence of sexual assault and rape (Paul & Gray, 2011). This information is critical because previous research has shown that men who commit sexually violent acts do not define their actions as coercive or manipulative (Heppner et al, 1995).…”
Section: Facts and Statisticsmentioning
confidence: 99%
“…Programmers must rely on the notion that attitude change has the potential to change future behavior. O'Donohue, Yeater, & Fanetti, (2003) reported that sexual violence is the result of multiple factors, one of which is directly connected to a person's internal inhibitions. This theory is based on the idea that one's perception and how they react to external stimuli is dependent on the regulation of their own thoughts and beliefs.…”
Section: Debunking Rape Mythologymentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome measures were based on the objectives of the program and taken from previous studies exploring determinants of sexual harassment. Previously identified determinants include gender attitudes (Abbey et al, 2001;McCauley et al, 2013), adverse sexual beliefs, attitudes about gender roles, acceptance of verbal pressure in obtaining sex (Abbey et al, 2001), rape myth acceptance, acceptance of interpersonal violence, adverse sexual beliefs, rape empathy, and self-efficacy regarding dealing with potentially abusive situations (O'Donohue, Yeater, & Fanetti, 2003). This paper describes the effect evaluation of a trial implementation of Make a Move in Dutch residential youth care.…”
Section: Introductionmentioning
confidence: 99%